Cellulosic Ethanol Production by Recombinant Cellulolytic Bacteria Harbouring pdc and adh II Genes of Zymomonas mobilis. (20th July 2012) - Piriya, P. Sobana; Vasan, P. Thirumalai; Padma, V. S.; Vidhyadevi, U.; Archana, K.; Vennison, S. John
Abstract : The ethanol fermenting genes such as pyruvate decarboxylase ( pdc ) and alcohol dehydrogenase II ( adh II) were cloned from Zymomonas mobilis and transformed into three different cellulolytic bacteria, namely Enterobacter cloacae JV, Proteus mirabilis JV and Erwinia chrysanthemi and their cellulosic ethanol production capability was studied. Recombinant E. cloacae JV was found to produce 4.5% and 3.5% (v/v) ethanol, respectively, when CMC and 4% NaOH pretreated bagasse were used as substrates, whereas recombinant P. mirabilis and E. chrysanthemi with the same substrates could only produce 4%, 3.5%, 1%, and 1.5 % of ethanol, respectively. The recombinant E. cloacae strain produced twofold higher percentage of ethanol than the wild type. The recombinant E. cloacae strain could be improved further by increasing its ethanol tolerance capability through media optimization and also by combining multigene cellulase expression for enhancing ethanol production from various types of lignocellulosic biomass so that it can be used for industrial level ethanol production.